U-PB GEOCHRONOLOGY OF CRYSTALLINE ROCKS OF VILSHAN MINE (MIDDLE BUG, UKRAINIAN SHIELD) - Stepaniuk, L.; Zagnitko, V.; Dovbush, T.; Kovalenko, N.; Zülzle О.; Yaskevych, T. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Geochronological studies of granitoids from the Vilshansky mine of Middle Pobuzhzhya were carried out. Zircons and monacites from plagiogneiss, plagiogranites and migmatites of the Bug complex were analyzed. As a result, it was established that the rock association, which consists of migmatites with numerous xenolites of biotite gneisses, plagiogneises, occasionally graphite-containing gneisses, amphibolites and biotites (Khashchuvate-zavalivska suite of the Bug series) and intersected with the veins of aplito-pegmatoid granites, was formed as a result of a large-scale manifestation of graniteization processes, which began not later than 2.02 billion years ago and ended about 2.0 billion years ago. The age of metamorphic host rocks corresponds to the Archean values of uranium-lead dating.